DOI: 10.5353/th_991044166181203414
|View full text |Cite
|
Sign up to set email alerts
|

Exploring metadiscourse in university lectures in Hong Kong

Abstract: Federated Graph Neural Network (FedGNN) has recently emerged as a rapidly growing research topic, as it integrates the strengths of graph neural networks and federated learning to enable advanced machine learning applications without direct access to sensitive data. Despite its advantages, the distributed nature of FedGNN introduces additional vulnerabilities, particularly backdoor attacks stemming from malicious participants. Although graph backdoor attacks have been explored, the compounded complexity introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 206 publications
(481 reference statements)
0
0
0
Order By: Relevance
“…Finally, the new error compensation methodology on a variety of workpiece profiles (cylindrical as well as complex curved profiles) machined with the same tool/work material combination and machining set up were tested. In each case, the diametral error was smaller than ± 5 µm after compensation, which is close to the same order of the repeatability of the machine [5].…”
Section: Diametral Error Compensation On a Cnc Turning Centersupporting
confidence: 78%
See 2 more Smart Citations
“…Finally, the new error compensation methodology on a variety of workpiece profiles (cylindrical as well as complex curved profiles) machined with the same tool/work material combination and machining set up were tested. In each case, the diametral error was smaller than ± 5 µm after compensation, which is close to the same order of the repeatability of the machine [5].…”
Section: Diametral Error Compensation On a Cnc Turning Centersupporting
confidence: 78%
“…It is common knowledge that dimensional errors on parts produced by machine are usually several times larger than the axis positioning repeatability of the machines. For instance, when a CNC turning center was tested, it was found that the maximum error was often in the range 50 to 100 µm although the positioning repeatability was only about 4 µm [5]. Thus, it appears that most industrial machines are working well below their accuracy potential today.…”
Section: Intelligent Error Compensation Strategy Through Integrating ...mentioning
confidence: 99%
See 1 more Smart Citation